Hepatitis B reactivation in patients receiving targeted therapies. Issue 10 (26th November 2017) - Chang, Cheng-Shyong; Tsai, Chien-Yu; Yan, Sheng-Lei
ABSTRACT: Objectives : Hepatitis B virus (HBV) reactivation may occur spontaneously, during or after antiviral therapy, or when receiving immunosuppressive chemotherapy. HBV reactivation has also been reported in cancer patients receiving targeted therapies, such as monoclonal antibody and mammalian target of rapamycin (mTOR) inhibitor. This review article is aimed to discuss the issue regarding chronic HBV reactivation in patients receiving targeted therapies, with a special focus on tyrosine kinase inhibitors. Methods: Using MEDLINE search, the literature relevant to hepatitis B reactivation, monoclonal antibody therapy and tyrosine kinase inhibitor was reviewed. Results: HBV-infected patients receiving tyrosine kinase inhibitors (TKIs) may develop HBV reactivation even with resolved HBV infection status. Although the exact mechanism of TKI-induced HBV reactivation remains unclear, off-target immunological effects of TKI may play an important role in contributing to HBV reactivation. Discussion: Further well-designed studies are necessary to find out the incidence and mechanism of HBV reactivation in patients receiving TKIs. Screening, monitoring and prophylaxis or pre-emptive antiviral therapy is mandatory in HBV patients who are going to receive immunosuppressive therapy or targeted therapy. Conclusion: HBV reactivation may occur in patients receiving monoclonal antibodies and TKIs, even with resolved HBV infection status. Although the exact mechanism of TKI-induced HBV reactivation remains unclear, off-target immunological effects of TKI may play an important role in contributing to HBV reactivation.